2013 IEEE International Conference on Services Computing 2013
DOI: 10.1109/scc.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Performance Interference among Consolidated n-Tier Applications: Sharing is Better Than Isolation

Abstract: Abstract-Performance unpredictability is one of the major concerns slowing down the migration of mission-critical applications into cloud computing infrastructures [4]. An example of non-intuitive result is the measured n-tier application performance in a virtualized environment that showed increasing workload caused a competing, co-located constant workload to decrease its response time [12]. In this paper, we investigate the sensitivity of measured performance in relation to two factors: (1) consolidated ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In distributed computing, the problem of having I/O NETWORK • I/O re-routing [19], [20], [21], [22] • Application-side I/O scheduling [1], [ performance variability due to sharing resources is wellknown and studied. Numerous papers analyze this problem for clouds [23], [24], [25]. In [24], Pu et al present a study of interference specifically for I/O workloads in the cloud in order to understand the performance factors that impact the efficiency and effectiveness of resource multiplexing and scheduling among VMs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In distributed computing, the problem of having I/O NETWORK • I/O re-routing [19], [20], [21], [22] • Application-side I/O scheduling [1], [ performance variability due to sharing resources is wellknown and studied. Numerous papers analyze this problem for clouds [23], [24], [25]. In [24], Pu et al present a study of interference specifically for I/O workloads in the cloud in order to understand the performance factors that impact the efficiency and effectiveness of resource multiplexing and scheduling among VMs.…”
Section: Related Workmentioning
confidence: 99%
“…In [24], Pu et al present a study of interference specifically for I/O workloads in the cloud in order to understand the performance factors that impact the efficiency and effectiveness of resource multiplexing and scheduling among VMs. In [25], the authors investigate the sensitivity of measured performance in relation to consolidated server specification of virtual machine resource availability, and burstiness of n-tier application workload. Their results show that an increasingly bursty workload also increases the performance loss among the consolidated servers, however, without being able to offer a solution.…”
Section: Related Workmentioning
confidence: 99%
“…In a contrary approach, Kanemasa et al [14] demonstrated that shortcomings of strict isolation can outweigh its benefits. They show that a 50-50 split of CPU resources between two concurrent VMs can yield lower performance than a fully-shared allocation (100% CPU for both).…”
Section: Related Workmentioning
confidence: 99%
“…Some studies also address multiple resources [9]- [11]. Proposed techniques for mitigating performance interference effects cover isolation of shared resources between concurrent VMs [1]- [3], [12], [13] or sharing-based resource allocations [5], [14].…”
Section: Introductionmentioning
confidence: 99%
“…A datacenter customer running the same VM on the same physical host at different times is likely to experience wide disparity in performance, depending on the resource consumption by other VMs that happen to be co-located on this host [11,15]. Conservatively, and at significant cost, datacenter operators elect to keep physical servers at low utilization levels, to minimize the possibility of adverse performance interactions between customer workloads.…”
Section: Introductionmentioning
confidence: 99%